The Effectiveness of Ethnoscience-Based Electronic Student Worksheet to Improve Critical Thinking and Scientific Literacy in Middle School Students - Erlina Kusnul Kotimah; Woro Sumarni; Arif Widiyatmoko; Agung Tri Prasetya; Ani Rusilowati (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking and scientific literacy must be cultivated and mastered by students in science learning in the 21st century. This research aims to determine the validity, feasibility, and effectiveness of increasing critical thinking and scientific literacy skills on ethnoscience-based electronic student worksheets developed focusing on additive material. The development of this ethnoscience-based electronic student worksheet followed the ADDIE model using mixed methods. Data collection methods included interviews, distribution of teacher and student questionnaires, tests, and documentation. The validity of ethnoscience-based electronic worksheets obtained a material validity value of 0.98 and a media validity value of 0.97, both of which met the valid and appropriate criteria. Ethnoscience-based electronic worksheets have been proven to be effective in increasing critical thinking competence with an N-Gain score of 0.86 and also effective in increasing scientific literacy competence with an N-Gain score of 0.87, both of which meet the high criteria. In summary, research on the development of an ethnoscience-based electronic student worksheet has been deemed to have a very high level of feasibility and validity and is highly effective in improving the critical thinking and scientific literacy of junior high school students.